(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis and Design of Inventory Control System for Frozen Fruits Raw Materials EOQ, Safety Stock, TIC at Bali Food Industry Company. Bali Food Industry is a company that produces fresh fruits into frozen fruit. Raw material inventory is a production factor that plays a very important role in the production process of a company, this is because raw materials support the smoothness and continuity of a production process in a company. This study aims to determine the economical ordering of raw materials (EOQ), Safety Stock, and total inventory costs at Bali Food Industry. In research that has been conducted at Bali Food Industry, it is known that the economical ordering of raw materials for frozen fruit raw materials in strawberries is 733,961 Kg. In mango, a total of 609,587Kg besides that in mixberry products with a total of 433,634 Kg. In the Safety stock analysis, it is known that the strawberry is 9.347,387 Kg. In mango fruit amounting to 6.166,726 Kg. The mixberry product is obtained at 2.739,885 Kg. In addition, the frozen Total Inventory Cost analysis obtained results on strawberry products amounting to Rp. 367.788.914 on frozen mango products amounting to Rp. 473.022.016 and on Mixberry obtained at Rp. 378.542.438. The system design in the form of templates with simple Microsoft Excel applications is made according to the needs of the company, namely producing EOQ, Safety Stock and Total Inventory Cost calculation templates, which can facilitate the company in determining the supply of raw materials for the smooth production process.